Djebba’s Cabaret - Tainon, Ghislaine Magouo (Journal of Anthropological Films, 2022)
Djebba’s cabaret is the portrait of a young brewer of bilbil (Traditional millet beer). Djebba is a young woman who has trained as a teacher but has been unable to find work for 05 years. To survive in a big city like Ngaoundéré (Cameroon), she brews and sells millet beer so that she can support herself. Despite the low profit of the brewing profession, she has won the loyalty of a large number of customers with whom she shares very familiar relationships. Djebba’s business allows her to live on a daily basis but she still hopes that one day she will finally be able to work as a teacher.